The Development of Quiet Book Media on the Ability to Recognize the Letters “b” and “d” in Children Aged 4–5 Years - Elvatiana, Vanni Widia; Widayati, Sri (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
Early childhood can be categorized into three different groups, namely children aged 0–2 years, children aged 3–5 years, and children aged 6–8 years. Recognizing letter shapes is the foundation of reading activities; therefore, it is important for parents and teachers to provide stimulation in recognizing letter shapes in children so that it can serve as preparation for the next level of education. This study aims to determine the feasibility of developing Quiet Book media on the ability of early childhood to recognize the letters “b” and “d,” and to determine the effectiveness of the developed Quiet Book media on the ability of early childhood to recognize the letters “b” and “d.” The research used the Research and Development (R&D) method. The product development design in this study referred to the ADDIE model developed by Branch. The research results showed Sig. value of 0.001 < 0.05, thus H₀ was rejected and H₁ was accepted. This means there is a significant difference between pretest and posttest results, so it can be concluded that the Quiet Book learning media is effective in improving early literacy skills of children aged 4–5 years, particularly in recognizing the letters “b” and “d".